Analisis Putusan Hakim Dalam Kasus Tindak Pidana Pencurian (Studi Putusan Nomor 1287/Pid.B/2023/PN Mdn) (International Forum of Researchers and Lecturers, 2023)
The monetary crisis has greatly impacted Indonesian society, leading to a moral crisis. This can be seen from the increasing crime rate and unemployment. This tends to cause one of the crimes that often occurs, which is theft. The application of standard articles in cases with relatively small valued goods will certainly increase the piling up of cases and the prolonged handling of a case. Not infrequently, these cases are forced to be resolved in a long period of time and end up in the Supreme Court. This study aims to find out the decision of the Medan High Court Number 1287/Pid.B/2023/PN Mdn regarding theft. In this study, the author uses a normative juridical approach, which is an approach carried out by analyzing and interpreting theoretical matters regarding principles, legal interpretation and comparative law. The results of the analysis and discussion in this study are that in the case of the criminal act of theft with case number 1287/Pid.B/2023/PN Mdn, the Defendant, Tamim Hasyim Als Tamim, was found guilty by the Panel of Judges for committing the criminal act of